Bender–Gradual Scoring System: Performance of Brazilian and Peruvian Children. Issue 3 (June 2014) - dos Santos, Acácia Aparecida Angeli; Noronha, Ana Paula Porto; Rueda, Fabián Javier Marín; Segovia, José Livia
This is a transcultural study of a sample of Peruvian and Brazilian children using the Bender–Gradual Scoring System (B–SPG), which considers shape distortion as the only aspect to be analyzed, assuming that perceptual-motor maturity is independent of cultural context. The study verified that the scoring system has psychometric qualities such that it may be applied in another country. The sample consisted of 231 children, ages 6 to 10 yr., 108 from different districts of the province Lima in Peru, and 123 children from three states in Brazil. During test application, the figures were projected to children in groups. Scoring the protocols for errors was conducted by psychologists experienced in interpreting and correcting the Bender–SPG, who rigorously followed instructions in Portuguese and Spanish. The results obtained with Differential Item Functioning (DIF) analysis indicated that Figures 1 and 4 presented DIF, one favoring Brazilian children and the other Peruvian children. Thus, it was concluded that the overall scores did not favor either population and the Bender–SPG could be used to evaluate perceptual-motor maturity in both countries.